OPTIMALISASI ECENG GONDOK (Eichornia crassipes) FERMENTASI EM4 DALAM RANSUM ITIK ALABIO (Anas platyrhynchos Borneo) - Azhar Syafiq Imanullah; Herliani Herliani; danang biyatmoko; muhammad rido (AVES: Jurnal Ilmu Peternakan, 2025)
Water hyacinth (Eichhornia crassipes) is an abundant aquatic plant in South Kalimantan and has potential as an alternative feed, but its high crude fiber content is an obstacle to its use in poultry. Fermentation using Effective Microorganisms-4 (EM4) can improve the digestibility of this material. This study aimed to evaluate the effect of adding fermented water hyacinth to the diet on the performance of male Alabio ducks. The study used a completely randomized design with three treatments, namely P0 (0% fermented water hyacinth), P1 (20%), and P2 (30%), each with six replicates. The parameters observed included body weight gain, feed intake, and feed conversion ratio (FCR). The results showed that the control treatment produced the highest body weight gain, while feed intake increased with increasing levels of fermented water hyacinth. The best FCR value was obtained in the P0 (control) treatment, while the addition of 20–30% fermented water hyacinth increased feed intake but was not followed by an increase in feed utilization efficiency. It was concluded that the use of fermented water hyacinth in the Alabio Ducks (Anas platyrhynchos Borneo) ration needs to be limited to the optimal level in order to maintain productivity and feed efficiency.